Sistem Pendukung Keputusan Penentuan Lokasi Strategis Dalam Membangun Bisnis Usaha Menggunakan Metode Promethee II - Nursobah Nursobah; Reza Andrea (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Business is a very important activity in advancing the economy of a region, business development certainly requires a strategic location in building a good image and opportunity in a new place, often businesses that have developed experience destruction and even substantial losses due to a decision. in choosing the wrong new location can affect the development of the pace of business and the business as a whole, mistakes in choosing a business location can result in many unwanted risks occurring in the future, several internal and external risks that will affect the company if one chooses a strategic location, so it is important take a decision in choosing a strategic location in building a business using a system, the system is able to calculate several possibilities with predetermined criteria, the decision support system in this research uses the promethee II method, the method this is a method developed from the promethee method, this method has a higher level of accuracy. The results of this study selected location A as an alternative that has the highest rating level of 0,081659, it shows that this location is the best location to set up a business